SUBSURFACE GEOLOGICAL IMAGING OF ATAMBUA, WEST TIMOR BASED ON THE INTEGRATION OF MAGNETOTELLURIC (MT), GRAVITY, AND MAGNETIC METHODS - Wijanarko, Edy
Timor Island located in the eastern Indonesian archipelago has a complex geological structure related to its tectonic history. The tectonic history is recorded in the outcrops that show various types of deformation. Various tectonic models are proposed mainly based on regional geological and geophysical data. However, the available geophysical data to support geological studies on a more detailed scale are still very limited. Therefore, this study aims to map sub-basins and sub-regional sub-surface geological structures in Atambua, West Timor, and its surroundings using magnetotelluric (MT), gravity, and magnetic methods. The estimation of the geoelectrical strike direction from the phase tensor analysis and the lineament analysis on the gravity anomaly confirm that the regional structure orientation is Southwest - Northeast. The MT dimensionality analysis shows the validity for the 2-D approach in that direction. Based on the interpretation of the low gravity anomalies, two main basins that extend following the Southwest - Northeast trend have been identified, namely the Soe Basin and the Atambua Basin. Meanwhile, qualitative interpretation of magnetic anomaly shows the distribution of crystalline rocks which are not demagnetized are generally located in the southwest compared to crystalline rocks that are strongly demagnetized in the northwest, among sedimentary rocks that are evenly distributed in the study area. The modelling of 2-D MT as well as 2½-D and 3-D gravity from the selected profiles perpendicular to the direction of the regional structure depicts the main sequence and its boundaries, based on its resistivity and density, respectively. The integration of this model with magnetic anomaly and geological data produces a thick-skinned geological model which shows the rock sequence from the youngest (near the surface) to the oldest (deep) are: the Viqueque Sequence and Bobonaro Formation (orogeny), the Kolbano Sequence (post-rift), the Kekneno Sequence (syn-rift), and the basement (pre-rift) dominated by rocks with Australian affinity. The thickness and depth of the main rock sequences represent the regional basininfill sediments resulting from tectonic events on Timor Island. This study suggests that the best sequence of petroleum systems in the study area is Mesozoic, Paleozoic, and Cenozoic plays.